Effect of Date Fruit Consumption in Later Pregnancy on Length of Gestation, Labour and Delivery of Nulliparous Women - Hiba, Nafeesa; Nisar, Salma; Mirza, Zainab Abbas; Nisar, Sarah (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the effect of date fruit consumption in late pregnancy on the onset and progress of labour, the need for induction and augmentation, and delivery outcomes.Study Design: Randomized controlled trial (NCT05105893).Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan to Jun 2021.Methodology: One hundred and forty women were randomized into equal-strength Experimental and Control Groups (70 in each Group). The Experimental-Group included those pregnant females who were advised to consume seven dates per day from 35 weeks onwards till the spontaneous onset of labour. In contrast, the Control-Group comprised primigravidae who did not consume dates in later pregnancy.Results: Spontaneous onset of labour was reported in 59(84.2%) pregnant women of the Experimental-Group compared to 43(61.4%) of Control-Group. 55(78.5%) pregnant women who consumed date fruit had a spontaneous vaginal delivery,4(5.7%) required instrumental delivery, and 11(15%) ended up having a caesarean section, whereas 43 out of 70(61.4%) women of the Control-Group had a spontaneous vaginal delivery, 6(8.5%) had an instrumental vaginal delivery, and 21(30%) underwent a cesarean section.Conclusion: The patients who had consumed date fruit in later pregnancy had an improved Bishop score at the onset of labour, a shorter duration of labour, a lesser need for induction and augmentation of labour and more spontaneous vaginal deliveries.